ANALISIS PENGARUH FASE TUMBUH TANAMAN ECENG GONDOK TERHADAP KEMAMPUAN FITOREMEDIASI Cr 6+ PADA LIMBAH CAIR PERTAMBANGAN NIKEL (Jurnal Geomine, 2019)
The increasing development of the mining industry carries the risk of environmental pollution and damage. PT. Vale Indonesia Tbk. is one of the nickel mining companies in South Sulawesi Province. Mining activities of PT. Vale Indonesia Tbk. produce waste water contaminated with Cr6+ with the concentration of 0.56 ppm which is not in accordance with the quality standards of nickel mining wastewater listed in PERMENLH No.9/2006, then the necessary treatment is next. This study tried to use the phytoremediation method with phase growth parameters of water hyacinth plants against phytoremediation of Cr6+ and knowing pH absorption. In this study 3 treatments were carried out on wastewater, including treatment of one wastewater with water hyacinth phase growing young with plant height